Dialogic Basis of the Categories of “Openness” and “Tolerance” to the “Other” in Modern Political Discourse – Martin Buber and Gabriel Marcel - Kovalchuk, Mykhailo; Shypunov, Hennadii (Studia Warmińskie, 2021)
The article analyzes the dialogical nature of the concepts of “tolerance”, “freedom”, “openness”. The interpretation of the dialogical relationship and the appearance of “Other” in it as opposed to “I” through the prism of the concepts of M. Buber and G. Marcel are analyzed. The impact of philosophers of dialogue on the formation of the modern meaning of the concepts “tolerance”, “other”, “openness” is substantiated. The dialogical methodology of interpersonal communications as one of the options for political interaction is considered. The relation “I-You” and the relation “I-It” as principles of construction of mass communication and interpersonal interaction are investigated. The rise in understanding the “Other” in the context of the type of interaction with it is illustrated. The need for mutual openness to enable tolerance is established. Tolerance is seen as the mutual acceptance of two equal freedoms without a dichotomous division into primary and secondary. On the example of dialogic concepts of M. Buber and G. Marcel, the types of dialogical interaction with the “Other” and the possible interpretation of the “Other”, including its typology, are demonstrated. The influence of dialogic interpretation of intersubjective connection on the formation of modern European values is determined.